2017
DOI: 10.1111/jfb.13350
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of Psammobatis rutrum (Chondrichthyes: Arhynchobatidae) in south Brazil, south‐west Atlantic

Abstract: This study presents information on the reproductive biology of Psammobatis rutrum based on 55 males and 53 females obtained as by-catch from bottom trawlers off southern Brazil during July 2013 and September 2014 and includes a detailed description of the egg capsule. Total lengths (L ) ranged from 22·3 to 31·6 cm and most of the sample comprised larger individuals, although there were no sexual differences in length-frequency distributions. Significant sexual differences were found for total length-disc width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(76 reference statements)
0
2
0
1
Order By: Relevance
“…The development of the cusp of males' teeth of all three species coincides with sexual maturity: between 25 and 26 TL for P. extenta and P. rutrum and between 40 and 42 TL for P. lentiginosa (GOMES et al, 2010;PERIER et al, 2011;MARTINS;ODDONE, 2017). The analysis of the length/width ratio of symphyseal teeth in the adults of the three species examined here ( Figure 3) demonstrated that teeth in males can be almost twice as long as wide.…”
Section: Discussionmentioning
confidence: 60%
“…The development of the cusp of males' teeth of all three species coincides with sexual maturity: between 25 and 26 TL for P. extenta and P. rutrum and between 40 and 42 TL for P. lentiginosa (GOMES et al, 2010;PERIER et al, 2011;MARTINS;ODDONE, 2017). The analysis of the length/width ratio of symphyseal teeth in the adults of the three species examined here ( Figure 3) demonstrated that teeth in males can be almost twice as long as wide.…”
Section: Discussionmentioning
confidence: 60%
“…Alcançam até 32 cm de comprimento e os machos atingem maturidade sexual entre 23 e 27 cm. São ovíparas e depositam ovos pequenos (<30 mm) (Mabragaña et al, 2011;Last et al, 2016;Martins & Oddone, 2017). Alimentam-se predominantemente de crustáceos e ocasionalmente de peixes e poliquetos (Viana, Valentin & Vianna, 2017).…”
Section: Introductionunclassified
“…The latter was described based on a single female collected around Malvinas/Falkland Islands, whose external morphological characteristics and skeletal structures, particularly the scapulocoracoid, were unique (McEachran, 1983). After the revision of McEachran (1983), several studies were conducted on almost all Psammobatis species including reproductive biology (Braccini and Chiaramonte, 2002b;Mabragaña and Cousseau, 2004;San Martín et al, 2005, Mabragaña, 2007Perier et al, 2011;Mabragaña et al, 2012;Martins and Oddone, 2017), feeding ecology (Braccini and Perez, 2005;Mabragaña, 2007;Mabragaña and Giberto, 2007;San Martín et al, 2007;Barbini and Lucifora, 2012), morphology (Braccini and Chiaramonte, 2002a;Mabragaña, 2007), egg cases (Concha et al, 2009;Mabragaña et al, 2011;Vazquez et al, 2016), and their parasites community (Irigoitia et al, 2019). Strikingly, no further studies were conducted in P. parvacauda.…”
Section: Introductionmentioning
confidence: 99%